Exercise Training Preserves Myocardial Strain and Improves Exercise Tolerance in Doxorubicin-Induced Cardiotoxicity - Gomes-Santos, Igor L.; Jordão, Camila P.; Passos, Clevia S.; Brum, Patricia C.; Oliveira, Edilamar M.; Chammas, Roger; Camargo, Anamaria A.; Negrão, Carlos E. (Frontiers in Cardiovascular Medicine, 2021)
Doxorubicin causes cardiotoxicity and exercise intolerance. Pre-conditioning exercise training seems to prevent doxorubicin-induced cardiac damage. However, the effectiveness of the cardioprotective effects of exercise training concomitantly with doxorubicin treatment remains largely unknown. To determine whether low-to-moderate intensity aerobic exercise training during doxorubicin treatment would prevent cardiotoxicity and exercise intolerance, we performed exercise training concomitantly with chronic doxorubicin treatment in mice. Ventricular structure and function were accessed by echocardiography, exercise tolerance by maximal exercise test, and cardiac biology by histological and molecular techniques. Doxorubicin-induced cardiotoxicity, evidenced by impaired ventricular function, cardiac atrophy, and fibrosis. Exercise training did not preserve left ventricular ejection fraction or reduced fibrosis. However, exercise training preserved myocardial circumferential strain alleviated cardiac atrophy and restored cardiomyocyte cross-sectional area. On the other hand, exercise training exacerbated doxorubicin-induced body wasting without affecting survival. Finally, exercise training blunted doxorubicin-induced exercise intolerance. Exercise training performed during doxorubicin-based chemotherapy can be a valuable approach to attenuate cardiotoxicity.